The Influence of Attitudes, Subjective Norms, and Perceived Behavioral Control of Commuter Intentions to Use Public Transportation in Greater Bandung, Indonesia - Cariera, David; Joewono, Tri Basuki; Belgiawan, Prawira Fajarindra (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2023)
Although public transport provides many benefits, such as a cleaner environment, reduced congestion, and increased sustainable transportation, many people still prefer private transport. This motivates the exploration of users’ intention to choose and use public transportation. This study explores the psychological factors of public transport users based on the theory of planned behavior (TPB). TPB assumes behavior built because of the intention. Attitude (ATT) does not determine the intention to influence behavior directly but through a combination of Subjective Norms (SN) and Perceived Behavioral Control (PBC). Responses from public transport users in Greater Bandung were collected using a questionnaire. The results show that attitude (ATT) is the most vital factor that positively influences user intention, based on standardized estimates of 0.866 (ATT), 0.301 (PBC), and 0.202 (SN). Environmental and climate issues have the most significant influence on user attitudes when compared to quality factors sorted by standardized estimated values such as travel time, safety, and fare. Previous research revealed that the dominant factor was quality, but in this study, it switched to factors of transportation activities that affect the environment. In fact, the factor of ease of use and encouragement of information media is crucial to be considered by stakeholders.